Social Media Charity Campaigns and Pro-social Behaviour. Evidence from the Ice Bucket Challenge - Andrea Fazio; Tommaso G. Reggiani; Francesco Scervini (Institute of Labor Economics (IZA), 2023)
Social media use plays an important role in shaping individuals' social attitudes and economic behaviours. One of the first well-known examples of social media campaigns is the Ice Bucket Challenge (IBC), a charity campaign that went viral on social media networks in August 2014, aiming to collect money for research on amyotrophic lateral sclerosis (ALS). We rely on UK longitudinal data to investigate the causal impact of the Ice Bucket Challenge on pro-social behaviours. In detail, this study shows that having been exposed to the IBC increases the probability of donating money, and it also increases the amount of money donated among those who donate at most 100. We also find that exposure to the IBC has increased the probability of volunteering and the level of interpersonal trust. However, all these results, except for the result on the intensive margins of donations, are of short duration and are limited to less than one year. This supports the prevalent consensus that social media campaigns may have only short-term eects.
Keywords: D64; O35; 330; donations; volunteering; altruism; social media campaigns; Ice Bucket Challenge